Heat-pretreated Lactobacillus rhamnosus GG shows enhanced survival capacity after spray drying. Issue 16 (12th December 2022) - Broeckx, Géraldine; Kiekens, Shari; Jokicevic, Katarina; Byl, Eline; Henkens, Tim; Vandenheuvel, Dieter; Claes, Ingmar; Lebeer, Sarah; Kiekens, Filip
Abstract: Recently, research in the probiotic field is attracting attention worldwide, also in the pharmaceutical industry. New insights are gained about the functionality of beneficial bacteria, like Lactobacillus rhamnosus GG, and their role in health and disease. It is therefore also important to study the impact of industrial processing techniques on the viability and functionality of probiotics. Different stresses, that hamper bacterial viability, are inherent to different processing techniques. As probiotics need to be alive and active by definition, the manufacturing of successful pharmabiotics remains challenging. Therefore, it is interesting to assess the effect of strategies that improve bacterial viability after spray drying. In this study, heat pretreatment of Lactobacillus rhamnosus GG enhanced bacterial viability with one log-unit after spray drying. Finally, Lactobacillus rhamnosus GG proved to have the capacity to develop resistance to consecutive spray-drying cycles, creating a more robust strain of Lactobacillus rhamnosus GG.